Does Green Credit Policy Move the Industrial Firms Toward a Greener Future? Evidence From a Quasi-Natural Experiment in China - Xiao, Zumian; Yu, Lu; Liu, Yinwei; Bu, Xiaoning; Yin, Zhichao (Frontiers in Environmental Science, 2022)
How to reduce pollutant emissions with green finance policies has been a focal topic in recent years. Taking the green credit pilot policy as a “quasi-natural experiment”, the propensity score matching and difference-in-difference approach (PSM-DID) are used to investigate the impact of the green credit policy implemented by Chinese government on SO2 emissions of firms. The empirical results indicate that the green credit policy significantly reduced corporate SO2 emissions. Heterogeneity analysis shows this impact is more pronounced for large-scale enterprises and enterprises in the eastern region. The mediation effect analysis reveals that after the implementation of the green credit policy, enterprises mainly achieve reductions in SO2 emissions by increasing environmental investment and reducing energy consumption intensity. Moreover, the green credit policy is also significantly effective in mitigating the discharge of other common industrial pollutants. Our findings highlight the importance of green credit policies in achieving greener industrial production and more sustainable economic development.